Manajemen Kepala Sekolah dan Peran Guru dalam Meningkatkan Kualitas Peserta Didik di MIN 1 Bandung - Mufatihatut Taubah; Imro’atul Nur Hidayah; Yulia Farikha Nurshofia; Suti’ah; Muhammad Dimas Saputra H.; Evi Wijayanti (QuranicEdu: Journal of Islamic Education, 2022)
The profesionalism of a school principal was a reflection for educators and education staff in improving the quality of education in schools. The purpose of this research was to find out how the profesionalism and leadership management of Madrasah heads at MIN 1 Bandung are highly respected by everyone because of their wisdom and profesionalism, The role of teachers in guiding students at MIN 1 Bandung, so that they won many awards in the field. national and international. This research was a qualitative research with interview and observation method. The results of the research revealed that all schools were required to understand all forms of school needs, so that the competence of educators and educators experienced significant growth and development. With that, the profesionalism of educators and education staff could be realized properly and correctly. Profesional education personnel of course not only master teaching materials, fields of science, and appropriate methods, but they had to be able to motivate students to have high skills and broad insight into the world of education.